Assessment of risk factors associated with outbreak of hepatitis A in Shakrial, Rawalpindi, Pakistan - Badar, Aamir; Malik, Muhammad Wasif; Hasnain, Syed Zain; Shah, Syed Ijaz Ali; Shabbir, Rana Muhammad Kamran; Haider, Waseem; Ahmed, Haroon (The Journal of Infection in Developing Countries, 2023)
Introduction: Two patients with jaundice reported to the National Institute of Health (NIH), Islamabad from Shakrial, Rawalpindi in April 2017. An outbreak investigation team was formulated to assess the disease magnitude, risk factors and control measures. Methodology: A case-control study was conducted in 360 houses in May 2017. The case definition was: onset of acute jaundice with any symptom including fever, right upper-quadrant pain, loss of appetite, dark urine, nausea and vomiting among Shakrial residents from March 10 - May 19, 2017. Four age and gender matched controls were selected for each case. Blood samples were sent to the NIH for laboratory confirmation. Frequencies, attack rates (AR), odd ratios, and logistic regression were computed at 95% confidence interval and p < 0.05. Results: A total of 25 cases (23 new) were identified with mean age 8 years and male to female ratio 1.5:1. Overall AR was 1.39% and the most severely affected age-group was 5-10 years (AR of 3.92%). Multivariate analysis revealed that raw vegetable consumption, lack of awareness and poor handwashing practices had significant association with disease spread. All blood samples were positive for hepatitis A, and no resident was previously vaccinated. Lack of awareness of disease spread among the community was the most probable reason for the outbreak. There were no new cases during follow up until May 30, 2017. Conclusions: Healthcare departments should implement public policies towards the management of hepatitis A in Pakistan. Health awareness sessions and vaccination for children ≤ 16 years age is recommended.